Asuhan Kebidanan pada Akseptor KB Suntik DMPA dengan Kenaikan Berat Badan di Klinik KIA Bapelkes Pemda DIY 2014 - Fauziah, Arvicha (STIKES 'Aisyiyah Yogyakarta, 2014)
THE MIDWIFERY CARE OF DMPA INJECTION CONTRACEPTION ACCEPTOR WITH INCREASING OF WEIGHT IN BAPELKES YOGYAKARTA DISTRICT’S CLINIC, 20141 Arvicha Fauziah2, Sri Lestari3 ABSTRACT Background: The DMPA injection contraception has high side effect, that is weight increase. The data of 3 month injection contraception acceptor is 30,13%, having weight increase about 1-5 Kg. The other way, 69, 87% has weight increase about 6-10 Kg. The purpose of this research is to find out the midwifery care of DMPA injection contraception with increasing of weight in BAPELKES YOGYAKARTA DISTRICT’S CLINIC, 2014. Method: The type of this research is a qualitative research. This Research design used case study. The type of data research is primary data. It used interview result and direct observation. The secondary data of this research used documentation study and literature study. The equipment of data collection used non-test method, that were interview guide, observation, and SOAP format with Varney’s mindset and document record. Result: The writer did this research for 2 weeks, and found the cause of Mrs. T’s weight body increase is DMPA contraception. Besides, the other factors were gen, activity, and nutrition. On December, 20th 2011, Mrs. T’s weight body was 62 Kg, and it was to be 66 Kg on July, 10th 2014. Mrs. T experienced the weight body increase almost 4 Kg for 3 years. The change weight of Mrs. T’s had the fluctuated in lowest weight was 60 Kg on March, 22nd 2012. On other side, the highest weight was 68 Kg on January, 23rd 2014, so Mrs. T had ever experienced the weight increase almost 8 Kg. The midwirefy care of DMPA injection contraception was giving conseling to overcome the side effect of using DMPA injection contraception and giving advice to do low calory diet. Conclusion: In giving of midwifery care of injection contraception acceptor with increasing of weight, the writer did not find some differences between theory and the case. Suggestion: To DMPA injection contraception acceptor with increasing of weight is suggested to do diet program, in order the weight condition is still normal or ideal. If there is a grievance, please come to the health officer. Keyword : DMPA, Increasing of weight Bibliography : 31 books, 5 journals, 10 websites, 6 student’s thesis (2004-2013) Total Pages : xii, 90 pages, tabel 1, picture 1